2017
DOI: 10.1038/tp.2017.142
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin33 deficiency causes tau abnormality and neurodegeneration with Alzheimer-like symptoms in aged mice

Abstract: Late-onset Alzheimer’s disease (AD) remains a medical mystery. Recent studies have linked it to impaired repair of aged neurons. Potential involvement of interleukin33 (IL33) in AD has been reported. Here we show that IL33, which was expressed by up to 75% astrocytes in the aged brains, was critical for repair of aged neurons. Mice lacking Il33 gene (Il33−/−) developed AD-like disease after 60–80 weeks, which was characterized by tau abnormality and a heavy loss of neurons/neurites in the cerebral cortex and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 58 publications
7
65
0
Order By: Relevance
“…The aMCI and AD patients lacking IL-33 expression revealed signi cantly cognitive decline, while the patients with IL-33 expression preserved their cognitive function over 1-year period. This nding was consistent with the bidirectional relationship between IL-33 de ciency and neurodegeneration in several studies, including : (1) mice lacking IL-33 had persistent in ammation and severe neurodegeneration in retinal detachment [30]; (2) IL-33 de ciency mice failed to repair deoxyribonucleic acid damage of aged neuron, resulting in neurodegeneration and tau abnormality [19]; (3) mice lacking IL-33 were found to have impaired recovery after CNS injury [16]; and (4) IL-33 treatment rescued contextual memory de cits in AD mouse models [18]. Collectively, our study provided the rst human evidence that linking IL-33 to neurodegeneration in the aMCI and AD patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The aMCI and AD patients lacking IL-33 expression revealed signi cantly cognitive decline, while the patients with IL-33 expression preserved their cognitive function over 1-year period. This nding was consistent with the bidirectional relationship between IL-33 de ciency and neurodegeneration in several studies, including : (1) mice lacking IL-33 had persistent in ammation and severe neurodegeneration in retinal detachment [30]; (2) IL-33 de ciency mice failed to repair deoxyribonucleic acid damage of aged neuron, resulting in neurodegeneration and tau abnormality [19]; (3) mice lacking IL-33 were found to have impaired recovery after CNS injury [16]; and (4) IL-33 treatment rescued contextual memory de cits in AD mouse models [18]. Collectively, our study provided the rst human evidence that linking IL-33 to neurodegeneration in the aMCI and AD patients.…”
Section: Discussionsupporting
confidence: 87%
“…The CNS has the highest levels of IL-33 expression in all human organs [15][16][17], and recent basic and preclinical studies have reported its extend physiological and pathophysiological role in CNS development [17,19], recovery [16,28,29], and disease [15,18,21]. Here we further our understanding of the IL-33 in human AD research.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to this, Il33 shows highest expression levels in the central nervous system, being constitutively expressed in astrocytes, microglia, and oligodendrocytes (Liew et al 2016). Moreover, a deficiency for Il33 is associated with neurodegeneration and impaired repair of neurons in aged mice accompanied by memory loss and cognitive impairment, resembling an Alzheimer's disease-like phenotype, including tau abnormality (Carlock et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite suggestions from Wicher et al that IL-33 is only expressed in CNS during late embryogenesis and becoming absent in adult brain ( 17 ), others show that its expression is increased during postnatal development ( 16 , 18 ). IL-33 is also constitutively highly expressed in adult CNS tissues in both human and mouse ( 13 , 16 , 19 , 20 ).…”
Section: Diverse Expression Of Il-33 and Its Receptor St2 In Cns Regimentioning
confidence: 91%